Treatment outcomes and risk factors for an unsuccessful outcome among patients with highly drug-resistant tuberculosis in Ukraine - Pedersen, O. S.; Butova, T.; Kapustnyk, V.; Miasoiedov, V.; Kuzhko, M.; Hryshchuk, L.; Kornaha, S.; Borovok, N.; Raznatovska, O.; Fedorec, A.; Bogomolov, A.; Tkhorovskiy, M.; et al. (My University, 2024)
Objectives: To describe demographics, clinical features, and treatment outcomes of patients with highly drug-resistant tuberculosis (TB) in Ukraine, and to evaluate risk factors for an unsuccessful outcome. Methods: Data from patients with multi-, pre-extensively, or extensively drug-resistant TB were collected prospectively from TB dispensaries in 15 out of 24 Ukrainian oblasts (regions) from 2020 to 2021. Treatment outcomes were evaluated using WHO definitions. Risk factors for an unsuccessful outcome were identified using a multivariable logistic regression model. Results: Among 1748 patients, the overall proportion of successful outcomes was 58% (95% confidence interval [95% CI] 56e60) (n ¼ 1015/1748), ranging from 65% (95% CI: 62e69) (n ¼ 531/814) for multidrugresistant TB to 54% (95% CI: 49e58) (n ¼ 301/563) for pre-extensively drug-resistant TB and 49% (95% CI: 44e55) (n ¼ 183/371) for extensively drug-resistant TB. Results were similar across oblasts, with few exceptions. The strongest risk factors for an unsuccessful outcome were extensively drug-resistant TB (adjusted OR [aOR] 3.23; 95% CI: 1.88e5.53), total serum protein below 62 g/L in adults and below 57 g/L for children and adolescents (aOR 2.79; 95% CI: 1.93e4.04), psychiatric illness (aOR 2.79; 95% CI: 1.46 e5.33), age at TB diagnosis >65 years (aOR 2.50; 95% CI: 1.42e4.42), and alcohol misuse (aOR 2.48; 95% CI: 1.89e3.26).
Keywords: BPaL; COVID-19; Drug-resistant tuberculosis; Extensively drug-resistant tuberculosis; Multidrug-resistant tuberculosis; Pre-extensively drug-resistant tuberculosis; Risk factors; Treatment outcomes